Mobility for learners and staff - higher education students and staff mobility inter-institutional agreement 2014-2021 between programme countries Universitat Politècnica de València and Universidade Lusíada de Lisboa - Universidade Lusíada (2017)
- Cooperate for exchange of students and/or staff in the context of the Erasmus+ programme; - Erasmus subject area: Architecture.